Pengaruh Literasi Keuangan, Sikap Keuangan, Perilaku Keuangan, dan Kepribadian Terhadap Kinerja UMKM (Studi Kasus di Kabupaten Blitar) - Ashari, Ahmad Aziz Santoso; Diana, Nur; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2023)
This research aims to determine whether the independent variables of financial literacy, financial attitude, financial behavior, and personality have an influence on the dependent variable of SME (Small and Medium Enterprises) performance in the Blitar Regency area. The research employs a correlation research method with a descriptive approach. The total number of respondents is 103 individuals. Using descriptive analysis and multiple linear regression analysis, the findings indicate that financial literacy, financial attitude, financial behavior, and personality collectively have an impact on SME performance. Based on hypothesis testing using partial tests (t-test), it can be concluded that financial literacy has a positive influence on the performance of Micro, Small, and Medium Enterprises (MSMEs). Conversely, financial attitude does not have a significant influence on SME performance. Financial behavior does not significantly affect SME performance. Meanwhile, personality has a significant influence on SME performance.Keywords : Financial literacy, financial attitude, financial behavior, financial, personality, business performance